2021
DOI: 10.1371/journal.pone.0247447
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus risk perception and compliance with social distancing measures in a sample of young adults: Evidence from Switzerland

Abstract: The health risk of the coronavirus pandemic is age-specific. The symptoms of a COVID-19 infection are usually mild in the healthy population below the age of 65; however, the measures laid down to prevent the spread of the virus apply typically to the whole population. Hence, those who have a low risk of severe symptoms face a social dilemma in cooperating and complying with the safety measures: Cooperating in preventing the spread of the disease is good for society but comes with individual costs. These costs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
51
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 45 publications
(29 reference statements)
10
51
1
2
Order By: Relevance
“…Furthermore, mediation analysis showed that women and older participants reported higher levels of compliance with official pandemic guidelines. These results are consistent with previous research showing that women and slightly older participants were more likely to engage in health-protective behaviours Franzen & Wöhner, 2021;Galasso et al, 2020). As for the age effect, one possibility is that older people are more concerned about possible infection and perceive greater risk because symptom severity and mortality rates increase with age.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, mediation analysis showed that women and older participants reported higher levels of compliance with official pandemic guidelines. These results are consistent with previous research showing that women and slightly older participants were more likely to engage in health-protective behaviours Franzen & Wöhner, 2021;Galasso et al, 2020). As for the age effect, one possibility is that older people are more concerned about possible infection and perceive greater risk because symptom severity and mortality rates increase with age.…”
Section: Discussionsupporting
confidence: 91%
“…The sigh of relief brought about by the post-lockdown era had a serious effect on the younger age groups who, at that time, had a lower risk perception for contracting the infection, as seen in a study by Dillard et al [ 30 ]. The perceived low risk of infection by younger respondents may make them less cooperative and less compliant with the safety measures [ 34 ], thus encouraging the spread of the virus while putting a greater part of the population at risk of COVID-19 infections [ 29 , 30 ]. This finding could be attributable to the fact that younger people are the more active age group in any given population.…”
Section: Discussionmentioning
confidence: 99%
“…A Japanese study highlights the importance of awareness and knowledge as being informed about COVID-19 was associated with a more precautious behaviour (Shiina et al 2020 ). Based on a sample of students in Switzerland, Franzen and Wöhner ( 2021 ) found that personal interests in staying at home (i.e. having high-risk relatives) increased compliance.…”
Section: Introductionmentioning
confidence: 99%